The burden of German history, 1919-45 : essays for the Goethe Institute - Laffan, Michael (London : Methuen, 1989)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: 1918-1945.; geschiedenis; Nazisme; Duitsland